Geometric morphometrics throws light on evolution of the subterranean catfish Rhamdiopsis krugi (Teleostei: Siluriformes: Heptapteridae) in eastern Brazil. (20th October 2014) - Bichuette, Maria Elina; Rantin, Bianca; Hingst‐Zaher, Erika; Trajano, Eleonora
<x xml:space="preserve">Abstract</x> Rhamdiopsis krugi is a highly specialized troglobitic (exclusively subterranean) catfish from phreatic water bodies of caves located within two separated metasedimentary basins in the region of Chapada Diamantina, Bahia state, Brazil. In order to test the hypothesis of isolation with differentiation of the groups from the Una‐Utinga and Irecê metasedimentary basins, we compared five populations among themselves and with an epigean species of Rhamdiopsis. This was accomplished using geometric morphometrics, a powerful tool for detecting differences in body shape at population and species levels. All studied samples differed significantly from each other, the epigean sample being the most distinct and the Una Basin populations clustering together. Geological and hydrological barriers explain the differences among the subterranean populations. We discuss our results together with the autapomorphies found in R. krugi, which validate its monophyly. These results imply an old age for the R. krugi clade, more than 10 Myr; alternative hypotheses are also presented. We propose a two‐step vertical colonization model of the subterranean habitat through the hyporheic zone by an epigean ancestral, with a progressive acquisition of the autapomorphies characterizing R. krugi. For conservation purposes, the two differentiated sets of populations should be considered and referred to as R. krugi 'Una morphotype' and R. krugi 'Irecê morphotype'. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 114, 136–151.